Treatment and utilization of pulp industry residues using Short Rotation Forestry - Neinavaie, Fargam (2011)
Pulp and paper industry produce large amounts of waste annually. Pulp mill effluents are highly polluting and a subject of great environmental concern (Chaudhari et al., 2010). Due to the large volumes of waste generated, the high moisture content of the waste and the changing waste composition as a result of process conditions, sludge recovery methods are usually expensive and their environmental impact is still uncertain (Monte et al., 2008). All these, bring the great importance to find a new method to handle sludge. This experiment suggests an alternative method for treating sludge from pulp and paper industry. This experiment was conducted to investigate the tolerance of the plants when grown in such substrates, to determine any differences in growth performance when different substrates and clones were used, and to evaluate the fate of chemical compounds in the different substrates. Experiment implement in two parts. The first part of this study was a pot trial in greenhouse which was practiced as a pre-study to evaluate initially effects of sludge on plant growth. The second part was consisted of a field experiment carried out in the Iggesund pulp and paper mill, where the performance of willow plants with two different plant densities grown on two different substrates were examined. Plants did survive and established in the sludge in both parts. This successful survival indicates the possibility of application of this method.